AKIBAT HUKUM PUTUSAN MAHKAMAH KONSTITUSI TERHADAP PEMILUKADA BUPATI KABUPATEN TELUK WONDAMA PROVINSI PAPUA BARAT TAHUN 2020: Legal Consequences The Constitutional Court Ruling On The 2020 Election Regents Of Teluk Wondama District, West Papua Province - Raihan Pahrazi; Radian syam (Faculty of Law, Universitas Trisakti, 2024)
General Elections, or later known as Elections, are a means based on popular sovereignty with the function of electing the President and Vice President, members of the DPR, DPRD and DPD. During the Regional Head Election, problems such as disputes over the election and deputy regents. Wondama Bay, West Papua, the problem of which is contained in MK Decision no. 32/PHP.BUP-XIX/2021. The formulation of the problem discussed in this research is the causes of the decision to re-vote by the Constitutional Court as in MK Decision No. 32/PHP.BUP-XIX/2021 and what legal consequences arise from the re-voting after the intended Constitutional Court Decision. This research method includes normative legal research which is descriptive analytical in nature through the use of secondary data from the results of literature studies along with the results of interviews, then data is carried out qualitatively and conclusions are drawn based on deductive logic. The results of research and discussion show that violations by general election organizers took the form of double voting and double voter lists. Conclusion After the re-voting was carried out, the Regency General Election Commission determined the results in Decree No. 18/PL.02.7-Kpt/9207/KPU-Kab/IV/2021. that candidate pair number four was announced as the winner